2017
DOI: 10.1080/24694193.2017.1386973
|View full text |Cite
|
Sign up to set email alerts
|

Medical-Device Related Pressure Injuries to Children in the Intensive Care Unit

Abstract: Medical devices that are attached to children put pressure on their skin or mucous membranes, and the devices can lead to injuries. The objective of this study was to determine the effectiveness of injury-prevention guidance about children who need to have medical devices attached to their bodies as part of their treatment. The research used a randomized controlled trial method, along with a cross-over design in 50 respondents with age ranges from 1 day to 18 years. The control group was treated in accordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 10 publications
2
42
0
1
Order By: Relevance
“…Orogastric tube, paediatric pulse oximeter and orotracheal cannula were the most used. These data are consistent with study involving 50 hospitalised paediatric and neonatal patients, identifying that the most used devices were SpO2 probe, orogastric tube and endotracheal tube (Widiati, Nurhaeni, & Gayatri, ).…”
Section: Discussionsupporting
confidence: 89%
“…Orogastric tube, paediatric pulse oximeter and orotracheal cannula were the most used. These data are consistent with study involving 50 hospitalised paediatric and neonatal patients, identifying that the most used devices were SpO2 probe, orogastric tube and endotracheal tube (Widiati, Nurhaeni, & Gayatri, ).…”
Section: Discussionsupporting
confidence: 89%
“…In paediatrics, the following devices are particularly associated with DRPU. 103,104 : respiratory devices, casts and orthotics, intravenous arm boards, intravenous tubing, oximetry probes and cervical collars.…”
Section: Devicesmentioning
confidence: 99%
“…is is especially important in neonatal and pediatric patients admitted to critical care and during transport between units. 104 Devices applied to newborn and infants in an ICU may take up 25-30% of the body surface, underlining the importance of careful and consistent observation to prevent DRPU. Standard care based on expert consensus recommendations should be followed (Box 8).…”
Section: Key Aspects Of Drpu Preventionmentioning
confidence: 99%
“…5 Widiawati et al (2017) identified medical devices that were linked with pressure injury in the PICU of X hospital in Jakarta, including the endotracheal tube (ETT) in 13% of incidents, the orogastric tube (OGT) in 12% of incidents, the nasogastric tube (NGT) in 11% of incidents, and the oxygen saturation probe in 6% of incidents. 6 It can be concluded that prolonged immobilization and the challenge of positioning medical devices are major causes of pressure injury in the PICU.…”
Section: Introductionmentioning
confidence: 99%